Зразки кладок баштових будівель поселення Маслини - Котенко, В.В. (Археологія, 2013)
До наукового обігу вводяться архітектурні об’єкти — башти з поселення Маслини на околиці Херсонеської держави у Північно-Західній Тавриці. Рассмотрены особенности сооружения башен поселения Маслины в Северо-Западной Таврике, исследованные в 1972—1976 гг. Особенность херсонесских сельскохозяйственных усадеб по сравнению с другими северопричерноморскими центрами состоит в способе их застройки, где поселения возникли как укрепленные полифункциональные комплексы с башнями. В отношении застройки поселение Маслины делится на укрепленную западную и неукрепленных восточную части. Укрепленная часть располагалась на природном возвышении и имела форму прямоугольника размерами 50 × 80 м. На поселении открыто три башенных комплекса, расположенные в западной, южной и восточной частях укрепления. Северная башня с частью прилегающих помещений уничтожена морем. Рассмотрение техники возведения стен трех башен и сравнение их с другими центрами хоры Херсонеса Таврического позволяет утверждать, что и на далекой периферии Херсонесского государства практиковали традиционные приемы монументального строительства, как и в крупных центрах Северо-Западного Крыма. Discussed are the peculiarities of erecting the towers at Maslyny settlement in North-Western Taurica studied from 1972 to 1976. A distinctive feature of Chersonesan agricultural estates, comparing with other north Pontic centres, lays in a way they are built up, while the settlements appeared as fortified poly-functional assemblages with towers. Concerning its building up, Maslyny settlement is divided into the western fortified and the eastern unfortified parts. The fortified one situated on the natural eminence and had a shape of a rectangular 50 × 80 m. Three tower assemblages situated in the western, southern, and eastern parts of the fortification are discovered at the settlement. The northern tower with part of adjacent rooms is destroyed by the sea. Consideration of the technique of walls erecting in the three towers and their comparison with other centres at chora of Tauric Chersonesos allows the author to state that in the distant periphery of Chersonesan state the traditional methods of monumental building were practiced like in the large centres of North-Western Crimea.